Decellularization of living tissue using microwave chemical process for tissue-engineered scaffold applications - Noor Azmi, Azran Azhim; Narita, Y.; Muramatsu, K.; Morimoto, Y.; Tanaka, Masato (Springer Berlin Heidelberg, 2010)
Scaffolds play a key role in the process of regeneration and morphogenesis of tissue or organ. We have studied a novel application of microwave radiation to prepare decellularized tissue for tissue-engineered scaffolds. The aim of the present study is to investigate the possibility of microwave effects on decellularization of soft and cartilage tissues. The targeted tissues were decellularized using 2450 MHz of microwave radiation in pulse-circulated 0.9% sodium chloride constituent of 1% sodium deoxycholate solution. To evaluate tissue integrity and cell removal, we used hematoxylin-eosin staining and scanning electron microscope. To investigate the effect of microwave power on targeted sample, we evaluate the radiated microwave distribution in microwave oven using thermograpic camera. Histological results suggest that microwave power influenced the decellularization of samples. It is significantly decellularized, when compared with the other preparation methods. Due to distributions of microwave radiation in the oven are non-uniform, the efficiency of cell removal can be improved by fitting the sample at uniform distribution and higher radiation spot of microwave. In conclusion, combination of microwave radiation and chemically detergent process has potential to decellularize various tissues, even tendon tissue. However, optimization of electromagnetic field in the oven is needed to perform in the further study to improve the decellularization efficiency.